The ventilatory response to lowering potassium with dextrose and insulin in subjects with hyperkalaemia. - Paterson, D; Friedland, J; Oliver, DO; Robbins, P (1989)
Arterial plasma potassium concentration ([ K+]a) is increased during exercise. This change is sufficient to excite arterial chemoreceptors and stimulate ventilation (VE) in the anaesthetized cat. Moreover, changes in [K+]a and VE are highly correlated during exercise, however the contribution that [K+]a makes to the control of breathing in man is not yet known. Four otherwise relatively healthy male hyperkalaemic renal patients had their VE measured before, during and after an intravenous infusion of dextrose and insulin to lower their [K+]a. Thirty-six minutes after the infusion began [K+]a had been reduced by ca. 2 mM. Ventilation was virtually unchanged throughout the experiment. These results suggest that [K+]a does not significantly affect VE in this group of subjects. The assumptions that would need to be made to extrapolate this conclusion to the general population are discussed.